Does Blood Urea Nitrogen Level Predict Severity and High-Risk Endoscopic Lesions in Patients with Nonvariceal Upper Gastrointestinal Bleeding?. (2008) - Al-Naamani, Khalid; Alzadjali, Nabil; Barkun, Alan N; Fallone, Carlo A
Abstract : BACKGROUND: Nonvariceal upper gastrointestinal bleeding (UGIB) is a serious medical condition requiring prompt resuscitation and early endoscopic therapy in those with high-risk endoscopic lesions (HRLs). There are little or no data correlating sole blood urea nitrogen (BUN) level with the severity of nonvariceal UGIB or the presence of HRLs in the adult population. OBJECTIVES: To determine if the BUN level on presentation correlates with parameters of severity of UGIB (need for blood transfusion or intensive care unit [ICU] admission) or to the subsequent finding of HRL, and in so doing identify patients who will require early endoscopic intervention. METHODS: The Canadian Registry of patients with Upper Gastrointestinal Bleeding undergoing Endoscopy was used to identify patients enrolled from the McGill University Health Centre (Montreal, Quebec) who presented with or developed acute nonvariceal UGIB while admitted. All comparisons were performed using Student's t test or Wilcoxon's signed rank test, as appropriate. Logistic regression modelling using a stepwise method was performed to identify independent predictors of severe nonvariceal UGIB and HRL. RESULTS: Two hundred nine patients were enrolled in the study. The mean age was 67±18 years and 59.8% were male. The mean BUN level was 13.4±9.4 mmol/L. Univariate analysis demonstrated that the BUN level was a significant predictor of ICU admission (BUN 14.7±10.4 mmol/L versus 12.0±8.0 mmol/L, P=0.035). However, when adjusted for systolic blood pressure, BUN level became a weaker predictor of ICU admission, just failing to achieve statistical significance (OR 1.03, 95% CI 1.00 to 1.06; P=0.08). Univariate analysis also demonstrated that BUN level was not a statistically significant predictor of blood transfusion requirement (BUN 14.1±10.6 mmol/L versus 13.6±8.6 mmol/L, P=0.508), nor of HRL (BUN 14.2±10.7 mmol/L versus 12.9±8.6 mmol/L, P=0.605). CONCLUSION: In patients with nonvariceal UGIB, the BUN level at initial presentation is a weak predictor of the severity of UGIB as defined by ICU admission, but is not helpful in identifying patients with a HRL.